1967
DOI: 10.1002/zaac.19673510108
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the System CuMnO

Abstract: A T‐x‐section of the phase diagram is proposed for the system CuMnO in air between 750 and 1,400°C. From X‐ray and chemical analyses on quenched samples and from high‐temperature X‐ray diffraction studies the occurrence of the following phases is deduced: a cubic phase α‐Mn2O3, a phase CuxMn3−xO4+γ (0 ⩽ x < 0.2 and 0 < γ < 0.02) with a tetragonally deformed spinel structure, a cubic spinel phase CuxMn3−xO4+γ (0 ⩽ x ⩽ 1.03 and −0.08 < γ < 0.02), a crednerite‐like phase CuyMn1−yO (0.50 < y < 0.53) with monocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
2
39
1
Order By: Relevance
“…It was demonstrated that CuMnO 2 is unstable at 1150°C. This is quite consistent with previous results [8,18]. In situ high-temperature XRD measurements show that CuMnO 2 at high temperatures has rhombohedral structure, not monoclinic, contrary to earlier literature.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…It was demonstrated that CuMnO 2 is unstable at 1150°C. This is quite consistent with previous results [8,18]. In situ high-temperature XRD measurements show that CuMnO 2 at high temperatures has rhombohedral structure, not monoclinic, contrary to earlier literature.…”
Section: Methodssupporting
confidence: 92%
“…Driessens and Rieck [18] investigated the interaction of copper and manganese oxides in air between 750 and 1400°C and reported Cu 1?x Mn 1-x O 2 to be a credneritelike phase with monoclinic structure (0 \ x \ 0.06) and a delafossite-like phase with hexagonal structure (0.08 \ x \ 0.12). At 1060 ± 10°C, the delafossite structure was reported to decompose.…”
Section: Introductionmentioning
confidence: 99%
“…4e). The other formate samples could form Cu V Mn \V O (where x(1) homogeneous spinel phases under harder conditions (heating to temperature above 900-1000°C, then cooling at 700-800°C, and quenching in water), according to the scheme given in (14,19).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the phases formed from various mixtures of CuO Schmall and Mu¨ller mentioned the compound Cu 1+x Mn 1ÀxÀd O 2+d (x ¼ 0:06 and d ¼ 0:048) [11]. Driessens and Rieck have extended the temperature range investigating the interaction of CuO and MnO oxides in air between 750 and 1400 1C [12]. In addition to the phases cited above the authors reported on a solid solution Cu 1+x Mn 1Àx O 2 having a crednerite structure for 0pxp0:06 and a delafossite structure for 0:08pxp0:12.…”
Section: Introductionmentioning
confidence: 98%